Determinants of termination fees in mergers and acquisitions in Asia Pacific - Lu, Yang (2013)
With an increase in prominence of Asia Pacific as an M&A center, both Asian Buyers and Sellers will be looking to emulate their Western counterparts to structure deals with sophistication. With financial sophistication, deals tend to include a variety of deal protection feature. This paper is therefore interested in Asia Pacific Sell-Side Termination Fees, being fees given by the target to the bidder in the event that the target walks away from the deal, and in examining its different determinants.